First study on response of astrocytes in alevines of red-bellied pacu (Piaractus brachypomus) to subchronic exposure to chlorpyrifos and trichlorfon - Gisella Karina Holguín-Céspedes; Ángel Enrique Céspedes-Rubio; Iang S. Rondón-Barragán (Veterinary World, 2022)
Background and Aim: Organophosphate pesticides (OPs) used in agricultural production pose environmental and public health risks whenever non-target organisms are exposed to them. Oxon-type OPs, such as trichlorfon (TCF) and chlorpyrifos (CPF), are frequently used in Colombia and have been detected in water bodies in the vicinity of croplands; however, their effect on aquatic organisms, especially fish, is largely unknown. The neurotoxicity of OPs includes inhibition of esterase enzymes, neuronal damage, and increased glial reactivity. This study aimed to assess the astrocytic response in the brain tissue of juvenile red-bellied pacu (Piaractus brachypomus) exposed to TCF and CPF.